The effects different doses of Caffeine on functional characterizations of liver and kidneys in albino rats - Hassan Al-naaly, Ahmed Jassim (Al-Qadisiyah Journal of Pure Science, 2017)
This study was carried out to investigate the effect of different doses of Caffeine on body, kidneys, and liver weights ØŒBiochemical parameters (ALP, AST and ALT enzymes, as well as total protein ØŒalbumin ØŒUrea and Creatinine concentrations), and histological study of liver and kidneys . For this purpose twenty four adult male rats were divided randomly into equal four three as below: Animals of control were treated with drinking water for four weeks ØŒFirst group (T1) treated with drinking water and 12.9 mg/kg of body weight of Caffeine(effect dose) for four weeks while second group (T2) were treated with drinking water and )double dose) of Caffeine 12.9 mg/kg of body weight )for four weeks) .At the end of treatment, animals were weighted, and anesthetized, blood draw was done to biochemical tests, then animals were sacrificed and dissected, after that liver and kidneys ØŒ were eradication to weighted and prepared histological slide. The results revealed that the different concentrations of Caffeine led to significant decrease (P <0.05) in body weight in T1 and T2 comparison with control group, and significant decrease in ALT ØŒAST and ALP enzymes concentrations in T2 comparison with T1 and control group .Whereas no significant decrease in liver and kidneys weight in T1,T2 group comparison with control group. On the other hand there is significant increase (P <0.05) in Urea and Creatinine concentrations in T2 comparison with T1 and control group .The histopathological results revealed a extended in sinusoids in liver and changes in collecting tube in kidneys caused by Caffeine. From this study we concluded double dose of Caffeine led to effects on functional characterizations of liver and kidneys.